Polarization in strong-field ionization of excited helium. (15th November 2021) - Bray, A C; Maxwell, A S; Kissin, Y; Ruberti, M; Ciappina, M F; Averbukh, V; Figueira De Morisson Faria, C
Abstract: We analyze how bound-state excitation, electron exchange and the residual binding potential influence above-threshold ionization (ATI) in helium prepared in an excited p state, oriented parallel and perpendicular to a linearly polarized mid-IR field. Using the ab initio B-spline algebraic diagrammatic construction, and several one-electron methods with effective potentials, including the Schrödinger solver Qprop, modified versions of the strong-field approximation (SFA) and the Coulomb quantum-orbit strong-field approximation, we find that these specific physical mechanisms leave significant imprints in ATI spectra and photoelectron momentum distributions. Examples are changes of up to two orders of magnitude in the high-energy photoelectron region, and ramp-like structures that can be traced back to Coulomb-distorted trajectories. The present work also shows that electron exchange renders rescattering less effective, causing suppressions in the ATI plateau. Due to the long-range potential, the electron continuum dynamics are no longer confined to the polarization axis, in contrast to the predictions of traditional approaches. Thus, one may in principle probe excited-state configurations perpendicular to the driving-field polarization without the need for orthogonally polarized fields.